HARGA DIRI REMAJA PUTRI DAN HUBUNGAN SEKS PRANIKAH - Anis Ervina (Akademi Kebidanan La Tansa Mashiro, 2013)
The purpose of research to determine the factors that cause young girls to have premarital sex, picture of self-esteem girls who have premarital sex, and solutions that can be done to overcome it. This study uses literature to find references theory relevant to the case or the problems found. The results indicated that the reason teenage girls having sex before marriage is caused by various factors both internal and external. Therefore the presence of the parents to accompany their children through every stage of life is very important in the formation of character and behavior of adolescents.